2020
DOI: 10.1002/cncy.22368
|View full text |Cite
|
Sign up to set email alerts
|

The “Brescia panel” (Claudin‐4 and BRCA‐associated protein 1) in the differential diagnosis of mesotheliomas with epithelioid features versus metastatic carcinomas

Abstract: Background The distinction between mesothelioma with epithelioid features and metastatic carcinoma may be challenging, particularly on cytology. A novel 2‐hit Claudin‐4 and BRCA‐associated protein 1 (BAP1) panel was investigated. Methods The objective of this study was to determine the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the panel on cytology from pleural effusions and matched biopsies, including 49 malignant mesotheliomas on cytology with 43 matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 31 publications
(82 reference statements)
6
31
0
Order By: Relevance
“…In order to maximize the diagnostic sensitivity and specificity of immunohistochemical markers, Bernardi et al [ 93 ] demonstrated that the coordinated use of two mesothelial negative biomarkers, namely claudin 4 and BAP1, had the best performance in differential diagnosis between epithelioid or biphasic mesothelioma and metastatic carcinomas. The expression of claudin-4 alone excluded MPM and double negativity was evident in all MPM.…”
Section: Unusual Morphologic and Immunohistochemical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maximize the diagnostic sensitivity and specificity of immunohistochemical markers, Bernardi et al [ 93 ] demonstrated that the coordinated use of two mesothelial negative biomarkers, namely claudin 4 and BAP1, had the best performance in differential diagnosis between epithelioid or biphasic mesothelioma and metastatic carcinomas. The expression of claudin-4 alone excluded MPM and double negativity was evident in all MPM.…”
Section: Unusual Morphologic and Immunohistochemical Featuresmentioning
confidence: 99%
“…This study summarized previous experiences singly investigating claudin-4 and BAP1 [ 94 , 95 , 96 , 97 , 98 ], and was performed on cell blocks and the corresponding pleural biopsies. In a practical algorithm [ 93 ], BAP1 and claudin-4 seems to represent the best panel for differentiating MPM with epithelioid features and metastatic carcinoma either on cytology or biopsy. More recently, cytoplasmic loss of methylthioadenosine phosphorylase (MTAP) has emerged as a specific marker of malignancy in mesothelial proliferations [ 99 , 100 , 101 ].…”
Section: Unusual Morphologic and Immunohistochemical Featuresmentioning
confidence: 99%
“…Additional ancillary tests may then be employed as necessary. Further studies are expected to validate this promising approach [14,48].…”
Section: Mesothelial Proliferationsmentioning
confidence: 99%
“…Although the value of BRCA‐associated protein 1 (BAP1) and Claudin‐4 has been documented by many studies, Bernardi and colleagues were the first to draw attention to these 2 markers through their earlier publications. In this issue of Cancer Cytopathology , they propose the name of Brescia panel for the combination of these 2 markers 1 . The panel presents the opportunity to use only 2 markers, given the high sensitivity and specificity of the panel to differentiate between mesothelioma (BAP1‐negative/Claudin‐4–negative) from metastatic carcinoma (BAP1‐positive/Claudin‐4–positive).…”
mentioning
confidence: 99%
“…In this issue of Cancer Cytopathology, they propose the name of Brescia panel for the combination of these 2 markers. 1 The panel presents the opportunity to use only 2 markers, given the high sensitivity and specificity of the panel to differentiate between mesothelioma (BAP1-negative/Claudin-4-negative) from metastatic carcinoma (BAP1-positive/Claudin-4-positive).…”
mentioning
confidence: 99%